A checklist of insects, mites and rodents affecting stored products in Iran - M.J. Shahhosseini; K. Kamali (نامه انجمن حشره‌شناسی ایران)
This checklist is intended to serve as a reference for Iranian Entomologist particularly those in plant  quarantine and plant protection activities. It been compiled from personal observations and 1014 reports and published literatures concerning pests of stored products in Iran since 1943, particularly reports of Farah -bakhsh 1961 (89), Freeman 1958, 1977 (90,91) Gentry 1965 (93).More than 190 species have been grouped under 3 categories of Insects, Mites and Rodents, with reference to their scientific names, products attacked and local distributions in Iran. This summary included only the scientific names of pests of stored products in Iran with reference to their taxonomic orders and families as follows.